Documenting Clinical Ethics Consultation - Porter, Amanda (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
This short perspective piece is about the documentation of clinical ethics consultation in Canada. It is written at a time when the Canadian Association of Practicing Health Care Ethicists (CAPHE) is endeavoring to develop standards of practice for clinical ethics in Canada. This brief commentary is informed by my experience working in clinical ethics in three different provinces, but it is primarily an attempt to draw attention to the normative questions: How much and what kinds of information should be included in clinical ethics documentation? Where should ethics consultation reports be saved, and who should have access to them? These questions are, more fundamentally, about how we should balance concern for privacy, confidentiality, professional integrity, accountability and the promotion of trust. They are also about where clinical ethics fits within the broader Canadian health system.